PENGGUNAAN BARANG BUKTI ELEKTRONIK YANG DIJADIKAN ALAT BUKTI DALAM PERKARA PIDANA - Muhammad Helmawansyah (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT This study discusses electronic evidence in criminal evidence in positive Indonesian law. In Criminal Procedure Article 184 paragraph (1) it is stated that there are 5 valid pieces of evidence, namely Witness Information, Expert Statement, Letters, Instructions, and Defendant Information. It is on this basis that judges can issue case decisions, but as the times and technology become more sophisticated, electronic evidence becomes the judge's consideration in issuing decisions. The purpose of this study is to analyze the position and strength of electronic evidence in Indonesian Positive Law and identify the characteristics and analysis used so that the evidence as electronic evidence can be used in court proceedings. The method used in this study is a normative juridical approach. The results of this study indicate that electronic evidence is valid evidence that can be used in trials. This is because the evidence in article 184 paragraph (1) of the Criminal Procedure Code has expanded its meaning. However, electronic evidence is still not strong and can not stand alone required experts to analyze the authenticity of the electronic evidence. Keywords: Proof, Criminal Law, Electronic Evidence